A systematic review of health disparities research in deep brain stimulation surgery for Parkinson’s disease - Memon, Adeel A.; Gelman, Kate; Melott, Joseph; Billings, Rebecca; Fullard, Michelle; Catiul, Corina; Miocinovic, Svjetlana; Amara, Amy W. (Frontiers in Human Neuroscience, 2023)
Background: Deep brain stimulation (DBS) is the primary surgical intervention for Parkinson's disease (PD) patients with insufficient response to medication, significantly improving motor symptoms and quality of life. Despite FDA approval for over two decades, access to this therapy remains limited. This systematic review aims to evaluate the influence of gender, race/ethnicity, socioeconomic status, and age on health disparities associated with DBS for PD, providing an overview of current research in this field. Methods: A systematic literature search was conducted in PubMed/MEDLINE, Embase, Web of Science and Cochrane databases from 1960 to September 12th, 2023, following Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Studies that examine the disparities in accessing DBS among patients with PD were included, comparing different demographic factors. Findings were synthesized and presented narratively to identify and understand DBS disparities. Results: After screening for relevance, 25 studies published between 1960-2023 were included, with 16 studies meeting full-text review criteria. While reviewing the references of the 16 articles, two additional studies were included, bringing the total number of included studies to 18. Most studies originated from the United States (44%). The identified studies were categorized as identifying disparities, understanding disparities, or reducing disparities. The majority focused on identifying disparities (72%), while fewer studies delved into understanding the underlying factors (28%). No studies evaluated strategies for reducing disparities. The findings indicate that elderly, female, and Black people, as well as those from low socioeconomic backgrounds and developing countries face greater obstacles in accessing DBS for PD. Conclusion: This study highlights factors contributing to disparities in DBS utilization for PD, including race, gender, and socioeconomic status. Public health policymakers, practitioners, and clinicians should recognize these inequalities and work towards reducing disparities, particularly among vulnerable populations.